ISOLATION OF TARAXASTEROL AND STIGMASTEROL FROM THE AERIAL PART OF Centaurea perrottetii DC. (Asteraceae) - O.G. ADUKU; S.M. ABDULLAHI; M.I. SULE; I. ATIKU; J.V. ANYAM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Centaurea perrottetii is a well-known plant used in African traditional medicine for its wound healing, anti-inflammatory, anti-microbial, anti-oxidant as well as cytotoxic properties. Preliminary phytochemical screenings of the methanol extract of the aerial partof Centaurea perrottetii revealed the presence of triterpenes, flavonoids, steroids, tannins, saponins and carbohydrates. Extensive phytochemical investigation of the n-hexane fraction led to the isolation of a pentacyclic triterpenoid (taraxasterol) and a steroid (stigmasterol). The isolated compounds were characterised on the basis of spectral data obtained from IR, 1D,2D 1H- and 13C-NMRspectroscopy and comparison withreported literature data.To the best of our literature search, this is the first report of isolation of taraxasterol and stigmasterol from Centaurea perrottetii.